DUS evaluation of nine intersubgeneric hybrids of Paeonia lactiflora and fingerprint analysis of the chemical components in the roots - Xu, Shiyi; Liu, Weili; Liu, Xiubo; Qin, Chen; He, Lianqing; Wang, Panpan; Kong, Lingyang; Chen, Xi; Liu, Zhiyang; Ma, Wei (Frontiers in Chemistry, 2023)
Intersubgeneric hybrids of Paeonia lactiflora (Paeonia lactiflora pall., P. lactiflora.) cover a huge variety of systems in the genus Paeonia. In recent years, many studies have confirmed that the intersubgeneric hybrids of P. lactiflora. are rich in paeoniflorin and other medicinal ingredients, however, it has always proved difficult to clarify the medicinal value of the hybrids and whether they can be used for medicinal purposes. In this study, the consistency of the plant population was evaluated through DUS evaluation, in order to clarify whether the selected research materials had stability and consistency within the population and specificity between populations. The differences between the paeoniflorin contents in the roots of the nine intersubgeneric hybrids of the P. lactiflora. varieties and two medicinal varieties were critically compared. The differences in the chemical components of the roots of nine intersubgeneric hybrids of P. lactiflora. and reference medicine substances of P. lactiflora. and Paeonia anomala subsp. veitchii (Lynch) D. Y. Hong and K. Y. Pan (Paeonia veitchii Lynch., P. veitchii.) were explored via stoichiometric and chemical fingerprint high performance liquid chromatography analyses. The results showed that there were significant differences in the chemical compositions between the intersubgeneric hybrids of P. lactiflora. and the medicinal reference materials, and the contents of paeoniflorin were elevated such that the hybrids could be used as the raw material for extraction of paeoniflorin, thus providing an opportunity to explore the medicinal value of the hybrids. This study explored the key differential components among the varieties and provides a reference and basis for the study of the medicinal value and the identification of the intersubgeneric hybrids of the P. lactiflora. varieties.